Loyalty Programs. The Experience of Foreign Countries - ERZIBAT G. Gasanova (Учёт. Анализ. Аудит)
The article is dedicated to the detailed analysis of the current international practice of accounting of loyalty programs in compliance with the adopted International standard (IFRS) 15 “Revenue from Contracts with Customers”. The article contains a detailed analysis of the revenue accounting according to the IFRS15 international standard. The analysis includes a focus on particularly complex aspects of accounting. The author considers the order of keeping accounting (IFRS) of individual items of revenue in compliance with the newly adopted standard. The article also considers the order of accounting (IFRS) of the loyalty programs. The author focuses on the most complex aspects of accounting that the companies face in practice. The article also provides practical examples of the loyalty programs accounting, which are especially difficult in practice, and offers solutions to the arising problems.